Length-weight relationship in Clarias batrachus (Linn.) from the Brahmaputra river system - Goswami, Umesh C; Sarma, Nripendra Nath (Indian Journal of Fisheries, 2011)
The length to weight relationship shows an isometric pattern of growth in Clarias batrachus (Linn.), an endemic air-breathing cat fish of the Brahmaputra river system. The weight of the adult fish proportionately increases alrrost to the cube of its length. There is a remarkable difference between the exponential value of juvenile and adult fishes. The higher exponential value in the juvenile fishes indicates a better adaptability in the natural habitat of the Brahmaputra river system of the northeastern India